2021
DOI: 10.1108/bfj-09-2020-0879
|View full text |Cite
|
Sign up to set email alerts
|

Food losses and waste quantification in supply chains: a systematic literature review

Abstract: PurposeThe purpose of this paper is to systematically review and critically examine food losses and waste quantification in supply chain, especially in studies that tackle all the supply chain activities in a real context.Design/methodology/approachThis work employed a systematic literature review methodology on the extant literature focusing on peer-reviewed journal articles published from 2000 to 2019.FindingsA systematic analysis of 117 articles reveals that downstream supply chains are studied to a greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…These claims were in line with those described by FAO reports of 2011 and 2013 (FAO, 2011(FAO, , 2013. However, other reviews have observed that downstream FSCs are more studied than those upstream, case studies in developed countries are more abundant, and weight tends to be the main metric used to quantify FLW (Cahyana et al, 2019;Kafa and Jaegler, 2021). Additionally, although most reviews analyzed FLW generation trends from a worldwide perspective, a small group of these focused on specific regions or certain actors along the FSC.…”
Section: Other Reviews In the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…These claims were in line with those described by FAO reports of 2011 and 2013 (FAO, 2011(FAO, , 2013. However, other reviews have observed that downstream FSCs are more studied than those upstream, case studies in developed countries are more abundant, and weight tends to be the main metric used to quantify FLW (Cahyana et al, 2019;Kafa and Jaegler, 2021). Additionally, although most reviews analyzed FLW generation trends from a worldwide perspective, a small group of these focused on specific regions or certain actors along the FSC.…”
Section: Other Reviews In the Fieldmentioning
confidence: 99%
“…Other important points to be highlighted based on the analysis are that, according to Xue et al (2017), only a small bunch of industrialized countries, such as United States and the United Kingdom, are linked to most of the existing publications, and the use of secondary data is reported in over half of these studies, despite the inherent uncertainties. Moreover, Kafa and Jaegler (2021) claimed that downstream FSCs are studied to a greater extent than upstream FSCs, with a clear emphasis on consumer waste. In fact, they state that a majority of articles on FLW focus on only one supply chain activity, and on the fact that the main metric to quantify FLW is weight.…”
Section: Analyzing Food Production Models: Towards Qualitative Assess...mentioning
confidence: 99%
“…Around 40% of the trout is not consumed by humans and is discarded as industrial waste (Fiori et al 2012 ). Retailers and consumers also produce a significant amount of waste (Kafa and Jaegler 2021 ). Most wastes end up in landfills, causing environmental issues, while others are converted into by-products such as aquaculture and animal feed.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the reviews conducted to date addressed challenges within a specific type of FSC such as perishable food chains (Lemma et al, 2014), fresh fruit supply chains (Negi and Anand, 2015;Soto-Silva et al, 2016), agri-fresh food supply chains (Dania et al, 2018;Handayati et al, 2015;Siddh et al, 2017;and Feng et al, 2020), and cold chains (Chaudhuri et al, 2018;Mercier et al, 2017;Ndraha et al, 2018;Shashi et al, 2018). Other review papers focused on addressing a specific challenge faced by food chains such as FLW (De Oliveira et al, 2021;Kafa and Jaegler, 2021;Lemma et al, 2014;Soto-Silva et al, 2016), transparency (Wognum et al, 2011), quality (Chaudhuri et al, 2018;Mercier et al, 2017;Ndraha et al, 2018;Siddh et al, 2017), collaboration/coordination (Dania et al, 2018;Handayati et al, 2015), and sustainability (Akkerman et al, 2010;Wognum et al, 2011).…”
Section: Introductionmentioning
confidence: 99%